Dielectric studies of dispersions of carbon nanotubes in liquid crystal 5CB - Koval'chuk, A.; Dolgov, L.; Yaroshchuk, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The frequency dependences of the imaginary ε″ and real ε′ parts of complex
dielectric permittivity inherent to planarly aligned layers of nematic liquid crystals 5CB
doped with multiwalled carbon nanotubes (CNT) were investigated in a wide range of
frequencies (f = 10⁻²-10⁶
Hz) and CNT concentrations (c = 0-0.25 wt.%). It has been
shown that the studied frequency range can be divided in three parts according to
behavior of ε′ (f) and ε″ (f) curves. The low-frequency range (10⁻² < f < 10¹ Hz) reflects
the near-electrode processes in the cell. The ratio ε″/ε′ used to characterize these
processes sharply grows if the concentration of CNT exceeds 0.05 wt.%. The moderate
frequency range (10¹ < f < 10⁵
Hz) corresponds to the alternating current conductivity,
σАС. At the nanotubes concentration less than 0.025 wt.%, σАС does not depend on the
frequency that implies its ionic origin. In its turn, at the c ≥ 0.025 wt.%, σАС is a power
function of the frequency that is typical for electronic hopping mechanism. The transition
from the ionic to electronic conductivity can be explained by the percolation theory with
the critical concentration of nanotubes 0.031 wt.% and percolation parameter 2.5. The
high-frequency range (10⁵ < f < 10⁶
) is mainly attributed to dipole volume polarization.
For c < 0.05 wt.% such polarization is well described by the Debye equation. The time of
dielectric relaxation in this frequency range increases with nanotubes content. This is
explained by effective interaction of nanotubes with 5CB molecules.